Análise espacial dos acidentes de trânsito em um município de fronteira internacional - Valdez, Hugo Antonio Lemes (2021)
Introduction: Traffic accidents are a major public health problem worldwide, daily leading thousands of people to death and leaving thousands more with permanent or temporary sequelae. Brazil, in turn, is among the countries that have more cases of traffic accidents, being one of the main causes of deaths from external causes. The international border regions are no different from this reality, due to the characteristics of this region, it is even more complicated to intervene in this problem and make the transit safer. Objective: To analyze the spatial distribution of motor vehicle traffic accidents and the spatial distribution of these accidents in an international border municipality. Methodology: This is an ecological, quantitative and descriptive study, with secondary data on traffic accidents. Data were obtained from the information system of the Integrated Service for Emergency Trauma Care (SIATE), the data were tabulated in a Microsoft Excel spreadsheet (version 2016, Microsoft, USA) and processed using descriptive statistics in absolute numbers and percentages. The method adopted was based on geoprocessing, spatial analysis and analysis of the built environment, which will be carried out using a free program such as QGIS 2.18 (georeferencing and Kernel map), logistic regression. Results: During the study period, 4,897 cases of traffic accidents were analyzed, involving predominantly men (68.7%), aged 20-39 years (58.0%), occurring at intersections (43.8%). As for the built environment, it was verified that the accidents occurred predominantly in well-signposted places, with good lighting, with adequate road conditions, on a road with low or medium speed. The geographical distribution of accidents was diffuse, but attention was drawn to the concentration in the central region of the city and in the vicinity of the friendship bridge. Conclusion: The vast majority of victims were men, young (20-39 years), and risk areas were intersections and commercial and urban areas.